Effectiveness of Liquid Soap and NPK Fertilizer in Enhancing Bioremediation of Petroleum Hydrocarbon-Contaminated Soil - Nnadikwe Johnson; Iheme Chigozie (BIOS: Jurnal Informatika dan Sains, 2025)
The effectiveness of liquid soap and NPK fertilizer in enhancing bioremediation of petroleum hydrocarbon-contaminated soil was investigated. Artificially polluted soil with 1% density of crude oil was treated with emulsifier (liquid soap) and NPK fertilizers at 3 levels of 0, 1, and 2 ton/ha in 3 replicates. The soils were incubated at 30°C and 60% field capacity for 0-4 weeks. Results showed that the pH increased from 4.74-7.01, conductivity increased from 17.00-1873.00 µS/cm, and TPH decreased from 585.28-349.22 mg/kg. The application of liquid soap and NPK fertilizer increased the remediation of oil-contaminated soil, with a significant decrease in TPH content (from 585.28 mg/kg to 349.22 mg/kg) observed in the treatment with liquid soap. The results indicate that bioremediation is a viable strategy for remediating petroleum hydrocarbon-contaminated soil, and the addition of liquid soap and NPK fertilizer can enhance the process.